Allyl-Modified of Calix[4]resorcinarene Derivatives for HER2 Inhibition Agents: An In Silico Study - Fitria, Anggit; Kurniawan, Yehezkiel Steven; Ananto, Agus Dwi; Jumina, Jumina; Sholikhah, Eti Nurwening; Pranowo, Harno Dwi (Journal of Multidisciplinary Applied Natural Science, 2025)
Breast cancer is one of the deathliest cancer diseases for women, with high mortality cases. Since breast cancer cells overexpressed HER2 receptors, a computerized structure-based screening was conducted to identify potential HER2 inhibitors as an anti-breast cancer agent. This method can investigate the potency of proposed compounds as potential protein inhibitors. Researchers were interested in studying some synthetic macromolecules, i.e., allyl-modified calix[4]resorcinarenes, through in silico studies as HER2 inhibitors using molecular docking studies. Prospective protein-ligand complexes for HER2 inhibition were further investigated by molecular dynamics simulations for 200 ns on different binding pockets. The allyloxycalix[4]resorcinarene derivative (5A) was identified as the most potential HER2 inhibitor through a computational approach, including molecular docking studies and molecular dynamics simulations. The HER2-5A complex was relatively stable during the 200 ns molecular dynamics run. In addition, the hydrogen bonds formed between blind docking and molecular dynamics simulations are almost unchanged for the HER2-5A complex. The HER2-5A formed with two crucial amino acid residues, i.e., Asp845 and Asn850. Moreover, the data of the molecular dynamics simulations of compounds 5A and 2A demonstrate the stability of both complexes in different binding sites of HER2. These computational results are preliminary data for further synthesis and in vitro evaluation.